Competing or synergistic? An exploratory analysis of a blended relationship between logics in a dilemma of artisan product innovation - Van Dai Nguyen; Thi Tuyet Mai Nguyen; Quynh Hoa Nguyen (Cogent Business & Management, 2023)
The existing literature has focused on the exclusive relationship between institutional logics that are perceived as competing. The current study argues that multiple logics can co-exist in a blended relationship. The purpose of this study is to shed light on such a blended relationship between the alleged competing logics through the analysis of the institutional demands prescribed for artisan product innovation. A qualitative study with 15 semi-structured in-depth interviews as the main data source was conducted in Bát Tràng, a local artisan ceramic community in Hanoi, Vietnam. This exploratory study reveals that institutional logics show the mutual intersection of some attributes that pave for the existence of the blended relationship. In other words, the mutual intersection of two logics permits the agents to traverse such a blurry boundary between these two logics without incurring institutional conflicts. This study also offers future research agenda in an established literature of institutional logics.
Keywords: 650; artisan logic; artisan product; institutional logic; market logic; Vietnam